Diversity of web accessibility in tourism: evidence based on a literature review - Teixeira, Pedro (2022)
In the tourism industry, people with disabilities (PwD) are frequently excluded from certain activities. The Internet is one of the most used information sources for planning tourism trips. However, the level of accessibility of information disseminated by the tourism industry through websites is still very low.